Dancing barefoot : five short but true stories about life in the so-called space age - Wheaton, Wil (O'Reilly, 2004)
Examines life, love, the web, and the absurdities of Hollywood in these compelling autobiographical narratives. Based on pieces first published in Wil's blog, www.wilwheaton.net.